GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 28554976 species occurrences available in GBIF matching the query: Geometry: POLYGON((-180 -35,-180 -45,180 -45,180 -35,-180 -35)). The dataset includes 28554976 records from 944 constituent datasets: 8 records from Naturalis Biodiversity Center (NL) - Crustacea. 167 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Ghent University - Zoology Museum - Vertebrate collection. 48 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 24399 records from Plan de vertebrados de la Patagonia. 50655 records from International Barcode of Life project (iBOL). 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 2135 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 7 records from University of Calgary Herbarium. 13 records from Entocytheridae (Ostracoda) World Database. 2250207 records from OEH Atlas of NSW Wildlife. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 16948 records from A global database for the distributions of crop wild relatives. 146 records from A Review of the Jumping Spider Fauna (Araneae: Salticidae) of Chile. 6 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 186 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 1 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 1 records from Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans. 2 records from HUFU - Herbarium Uberlandense. 188 records from Phanerogamic Botanical Collections (S). 163 records from Mollusca collection of National Museum of Nature and Science. 1695 records from MVZ Herp Collection (Arctos). 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 2 records from PRECIS (KwaZulu-Natal Herbarium). 647 records from University of Vienna, Institute for Botany - Herbarium WU. 10 records from SANBI: DNA Banking(1987-2011). 3 records from UFG - Herbário da Universidade Federal de Goiás. 168 records from Colección de Entomología - Diptera - Ceratopogonidae. 36 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 1 records from Review of the genus Hannemania (Acari: Leeuwenhoekiidae) with description the two new species in amphibians from Chile. 5797 records from MVZ Mammal Collection (Arctos). 36376 records from Australian National Wildlife Collection provider for OZCAM. 35 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 2253 records from ecoscope_observation_database. 9 records from Coleção de Aves do Museu Nacional / UFRJ. 2548 records from LACM Entomology Collection. 1 records from Bryophyte herbarium, Tromsø Museum. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 34 records from IAC - Herbário do Instituto Agronômico de Campinas. 497 records from Bee Biology and Systematics Laboratory. 4 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 13833 records from Bottom Trawl Surveys: Catch and Effort Data For South East Australia, 1898-1996. 1 records from Portuguese Seaweeds. 1 records from Collection of Heteroptera. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 2847 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 8154 records from AntWeb. 144 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 352 records from CAS Entomology (ENT). 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 127 records from Zoology (Museum of Evolution - Uppsala). 1 records from Lissotes working-group. 4370 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 1 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 60 records from PlutoF platform observations. 3 records from TCWC Marine Invertebrates. 56 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 13 records from PRECIS. 182 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 9065 records from CSIRO Ichthyology provider for OZCAM. 4058 records from Fishbase. 1 records from Australian freshwater sponges with a new species of Pectispongilla (Porifera: Demospongiae: Spongillida). 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 17 records from UTEP Plants (Arctos). 2078 records from Occurrence records of southern African aquatic biodiversity. 1 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 38 records from SPF - Herbário da Universidade de São Paulo. 13 records from The Neotropical tanyderid Araucoderus gloriosus (Alexander) (Diptera, Tanyderidae), with description of the egg, larva and pupa, redescription of adults, and notes on natural history. 61 records from SANT Herbarium vascular plants collection. 157 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 103 records from New genera, species and records of Maeridae from Australian Waters: Austromaera, Ceradocus, Glossomaera, Hamimaera, Huonella gen. nov., Linguimaera and Maeraceterus gen. nov. (Crustacea: Amphipoda). 52 records from KUBI Mammalogy Collection. 16 records from Biological Reference Collections ICM CSIC. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 69 records from Colección de Entomología - Arthropoda. 9 records from UFP - Herbário UFP - Geraldo Mariz. 2 records from NPL collections. 11 records from Cercle des mycologues de Montréal Fungarium (CMMF). 10 records from ICN - Herbário do Instituto de Ciências Naturais. 3 records from Contributions to the knowledge of the biodiversity of Heteroptera (Insecta) in the Southern Cone, Argentina. 4091 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 582 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 112 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 1 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 2 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 4 records from The avian collection at the Natural History Museum, Oslo, Norway. 779 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 1 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 493 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 871 records from Lyman Entomological Museum (LEMQ). 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 2469 records from IMOS - AusCPR: Phytoplankton Abundance. 555363 records from SA Flora (BDBSA). 3 records from NCSM Fishes Collection. 47 records from Colección Herpetológica de la Patagonia. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 127 records from AM: Freshwater Invertebrates (1900-2005). 52 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 16 records from Culture Collection of Cryophilic Algae. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 4 records from Fundación Miguel Lillo - Colección Invertebrados. 437 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 67 records from DMNS Bird Collection (Arctos). 198 records from The Fish Collection at the Zoologische Staatssammlung München. 21 records from Coordinated Waterbird Counts. 1 records from GENT Lactarius Deliciosi. 1 records from Museu Paraense Emilio Goeldi Herbarium. 9 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 1 records from CESJ - Herbário Leopoldo Krieger. 1 records from Global compendium of Aedes albopictus occurrence. 6260 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 193 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 15 records from CUMV Fish Collection (Arctos). 1 records from Field Museum of Natural History (Zoology) Bird Collection. 1 records from Mycology herbarium, Tromsø Museum. 4 records from UAM Mammal Collection (Arctos). 207 records from IZIKO: Marine Invertebrate Collection (1900-2011). 51 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 54 records from Collection des Mollusques (BOUM). 55712 records from Reef Life Survey: Global reef fish dataset. 1 records from Systematics of the bubblegum corals (Cnidaria: Octocorallia: Paragorgiidae) with description of new species from New Zealand and the Eastern Pacific. 804 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 658214 records from Museum Victoria provider for OZCAM. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 6 records from Cowan Tetrapod Collection - Mammals. 138 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from Flora of tanzania. 6 records from MBM - Herbário do Museu Botânico Municipal. 32 records from International Collection of Microorganisms from Plants (ICMP). 103 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 6 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 1621 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 2 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 651 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 334276 records from SA Fauna (BDBSA). 7 records from BMSM Bailey-Matthews National Shell Museum. 4336 records from Field Museum of Natural History (Zoology) Mammal Collection. 3 records from MVZ Hildebrand Collection (Arctos). 4367 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 30 records from Lund Museum of Zoology (MZLU). 345 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 1 records from FCAB - Herbário Friburguense. 4 records from Crustacea ZMK. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 77 records from CAS Invertebrate Zoology (IZ). 31 records from Crustacea collection of National Museum of Nature and Science. 26348 records from IMOS - AusCPR: Zooplankton Abundance. 364 records from Tallinn Botanic Garden. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 644 records from Colección de Zoología Invertebrados - Otros invertebrados. 257119 records from Historical Bird Atlas. 64 records from UAM Bird Collection (Arctos). 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 2459225 records from BirdLife Australia, Birdata. 7733 records from Museum of Comparative Zoology, Harvard University. 30 records from Marine gastropod distribution from patagonian shallow waters. 9 records from Naturalis Biodiversity Center (NL) - Cnidaria. 1150485 records from Australia's Virtual Herbarium. 2 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 30 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 317 records from Ichthyology Collection - Royal Ontario Museum. 1722 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 3873402 records from EOD - eBird Observation Dataset. 1 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 55252 records from Tasmanian Museum and Art Gallery provider for OZCAM. 81317 records from iNaturalist Research-grade Observations. 3725 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 59 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 34 records from UCBG TAPIR Provider. 1248 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 2 records from Global caridean shrimp fauna. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 424 records from CONN. 4 records from HUCS - Herbário da Universidade de Caxias do Sul. 3039 records from CSIRO, fish surveys by the Soela, 1980s. 20 records from NYSM Birds. 145 records from Recent Invertebrates Specimens. 895 records from Invertebrates Collection of the Swedish Museum of Natural History. 4 records from KUBI Ichthyology Tissue Collection. 3 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 4618 records from Global Lacustrine Diatoms. 697 records from SAEON: Historical Research Survey Database (1897-1949). 4 records from Estonian Museum of Natural History. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 510 records from University of California Museum of Paleontology. 1359 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 1408 records from Mammals housed at MHNG, Geneva. 2 records from DMNS Marine Invertebrate Collection (Arctos). 6337 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr).. 43 records from ALCB - Herbário Alexandre Leal Costa. 1 records from HUSC - Herbário Unisanta. 1 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 101 records from mel. 120 records from Estonian University of Life Sciences. 21463 records from Essig Museum of Entomology. 615 records from CAS Ichthyology (ICH). 21 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 91 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 23 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 19 records from DMNS Mammal Collection (Arctos). 2 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 725 records from Southern right whales distribution in Bahía Nueva, Puerto Madryn, Argentina. 4 records from TNHC Ichthyology Collection. 3847 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 70 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 38 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 195 records from MVZ Bird Observations (Arctos). 934 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 34 records from Colección de Entomología - Auchenorrhyncha. 138 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc).. 61 records from Seaweeds records from Argentina and Uruguay. 452 records from Live benthic foraminifera in South Atlantic surface sediments. 293 records from Diveboard - Scuba diving citizen science observations. 149 records from Bryophyte herbarium, NTNU University Museum. 12 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2011. 1433 records from (Appendix Table 1) Relative abundances of calcareous nannofossil in the total assemblage of ODP Hole 177-1090D. 9522 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe).. 1911 records from Illinois Natural History Survey Insect Collection. 341 records from RV Investigator Voyage IN2016_T02 Seabird Observations. 207 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 34 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 2 records from VIC - Herbário da Universidade Federal de Viçosa. 1043 records from The Brown University Foraminiferal Data Base (BFD). 276 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 4 records from Revision of the ant genus Mayriella.. 62 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 67 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 14 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2012. 1145 records from Colección Ictiológica del CENPAT-CONICET. 184 records from Abundance of calcareous dinoflagellates of sediment core GeoB3603-2. 2183 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 215 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 127 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 41 records from (Table 2) Dinoflagellate cysts in surface sediment samples of Meteor cruises M20/2, M23/1, M34/2 and M34/2. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 5 records from Dinoflagellate cysts in surface sediment samples of Meteor cruises M20/2, M23/1, M34/1, M34/2, M34/3 and M34/4. 3411 records from naturgucker. 49 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 2313 records from CSIRO, Cruise SS200702, Marine Biodiversity Survey, Southeast Australia, 2007. 55 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 206 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 592 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 3 records from Cleveland Museum of Natural History.. 360 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn).. 11 records from CAS Mammalogy (MAM). 37 records from UMMZ Mammal Collection. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 5 records from Revision of southern African species of the anglerfish genus Chaunax (Lophiiformes: Chaunacidae), with descriptions of three new species. 35316 records from New Zealand Arthropod Collection (NZAC). 718 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2008. 45 records from (Table S2) Age determination of ODP Sites 202-1234 and 202-1235. 37 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2007. 56 records from (Table 2) Planktic foraminifera and their diversity indices of sediment surface samples from the Atlantic Ocean. 793 records from (Table 17) Benthic foraminifera in early Miocene sediments of DSDP Hole 90-593. 684 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 98 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 296 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 45 records from (Appendix Table 3) Distribution of live benthic foraminifera in surface sediments. 53 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 10 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 1 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 337 records from Tissues Specimens. 29 records from MfN - Fossil invertebrates Ia. 9 records from MfN - Fossil vertebrates IV. 10 records from MfN - Fossil plants (Cenophytic). 1 records from MfN - Fossil plants (Paleophytic). 4 records from MfN - Fossil vertebrates V. 77 records from Relative abundance of radiolaria in surface sediments. 60 records from Coccolithophorids in surface sediments of the South Atlantic. 1 records from ZFMK DORSA. 21 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 16 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 63 records from Coccolith percentage of surface sediment samples. 397 records from Coccolith percentage exclusive Emiliania huxleyi of surface sediment samples. 6 records from (Table 1) Coccolith percentage of surface sediment samples from the south-eastern South Atlantik. 197 records from Nanoplankton abundance at station GeoB2011-3. 170 records from Nanoplankton abundance at station GeoB2021-1. 56 records from Nanoplankton abundance at station GeoB2021-3. 1 records from Benthic hard-bottom communities abundance at Lilliguapy in 2011. 1006042 records from First Bird Atlas. 12 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 1374 records from UCT: South Africa Seaweeds(1905-2008). 29 records from Nannofossil abundance of Hole 29-282. 3 records from Nannofossil abundance of Hole 29-283A. 129 records from Nannofossil abundance of Hole 29-284. 4 records from Nannofossil abundance of Hole 29-284A. 1 records from Heteroptera. 149 records from SBMNH Vertebrate Zoology. 1 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 18 records from Bolus Herbarium Specimens Collection (1865-2009). 27 records from Nannofossil abundance of Hole 26-251. 41 records from Nannofossil abundance of Hole 26-251A. 51 records from Colección de Entomología - Curculionidae. 3 records from ASE - Herbário da Universidade Federal de Sergipe. 34 records from CM Herps Collection. 1025 records from CSIRO, Jack Makerel surveys, 1978. 36 records from UEC - Herbário da Universidade Estadual de Campinas. 23 records from (Table 2) Ostracode assemblages and environment characteristica of modern surface sediment samples from Patagonia, Argentina. 85 records from (Table I) Vital effect adjusted stable oxygen isotope ratios of Quaternary nannoplankton in DSDP Hole 90-593 from the Challenger Plateau, South Tasman Sea. 2 records from UWBM Herpetology Collection (Arctos). 1596 records from (Table 14) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-592. 1389531 records from NZ National Vegetation Survey occurrence data. 2 records from FUEL - Herbário da Universidade Estadual de Londrina. 62 records from MSB Parasite Collection (Arctos). 2 records from Zariquiey Collection. Biological Reference Collections ICM CSIC.. 2246 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 5058 records from Northern Territory Museum and Art Gallery provider for OZCAM. 308 records from Lichen herbarium, Oslo (O). 42 records from Planktic foraminifera counts of sediment core ELT48.022-PC. 53 records from Planktic foraminifera counts of sediment core ELT48.027-PC. 108 records from Planktic foraminifera counts of sediment core RC08-39. 130 records from Planktic foraminifera counts of sediment core RC11-120. 213 records from Planktic foraminifera counts of sediment core RC11-121. 48 records from ICN - Universidad Nacional de Colombia. 316 records from Planktic foraminifera counts of sediment core RC11-86. 297 records from Planktic foraminifera counts of sediment core RC14-7. 216 records from Planktic foraminifera counts of sediment core RC14-9. 5083 records from LACM Vertebrate Collection. 33 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 2 records from Colección Nacional de Equinodermos Mexicanos (ICMyL-DF, UNAM). 7 records from Collection Crustacea ZMG. 4 records from Insecta ZMK. 5 records from Jardin botanique de Montréal (JBM). 7 records from Akita Prefectural Museum:Hiroki Watanabe Collection of mollusca. 3558 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 2800 records from SOMBASE BIOCONSTRUCTORS. 96 records from IZIKO South Africa Museum Collection (1800-2013). 39 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 92 records from Biogeographic distribution of the Antarctic and Sub-Antarctic brachiopods (living forms). 58 records from Biogeographic distribution of Antarctic and sub-Antarctic Cumacea. 7 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 33 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 38 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 2 records from Antarctic Isopods. 8 records from Antarctic Marine Species Sequence Data. 2 records from Asteroids from French subantarctic islands: records from the Marion Dufresne MD03 expeditions. 30 records from SO-Polylist. 39 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 1 records from Collection Bryozoa - ZIM Hamburg. 1 records from Collection Cnidaria - ZIM Hamburg. 109 records from Collection Crustacea - ZIM Hamburg. 18 records from Collection Polychaeta - ZIM Hamburg. 39 records from Collection Hydrozoa - ZSM München. 2 records from Collection Bryozoa - ZMB. 9 records from Collection Cnidaria - ZMB. 237 records from Collection Crustacea - ZMB. 38 records from Collection Echinodermata - ZMB. 11 records from Collection Hydrozoa - ZMB. 63 records from Collection Porifera - ZMB. 43 records from Collection Vermes - ZMB. 1 records from Collection Ornithologie - ZSRO. 5 records from Collection Polychaeta - ZSRO. 5 records from Tiroler Landesmuseum Ferdinandeum. 93 records from The Fungal Collection at the Botanische Staatssammlung München. 4 records from Ant'Phipoda Database (New records). 51 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 5 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 428 records from The Lichen Collection at the Botanische Staatssammlung München. 34 records from The Exsiccatal Series "Triebel, Microfungi exsiccati". 724 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 14280 records from Tropicos Specimen Data. 5948 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for ODP Site 181-1123. 1896 records from British Antarctic Survey Argos satellite tracking data. 2178 records from Palynological estimation of ODP Hole 189-1172A. 259 records from SOMBASE PYCNOGONIDS. 281 records from (Table S1) Relative abundances of coccolithophore taxa in surface sediment samples from the Equatorial and Southeastern Pacific. 1380 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 9270 records from Western Australian Museum provider for OZCAM. 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 234 records from (Table 2) Selected planktonic foraminiferal species and other microfossil data for sedimentcore P69. 1024 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for ODP Site 181-1119. 2084 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for sediment core R657. 24 records from paleovertebrados. 174 records from SysTax - Zoological Collections. 1 records from The Peacock Spiders (Araneae: Salticidae: Maratus) of the Queensland Museum, including six new species. 709 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 808 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 114 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 15 records from Naturhistorisches Museum Mainz, Zoological Collection. 1085 records from SOUTHERN OCEAN ISOPODA. 16102 records from Natural History Museum (London) Collection Specimens. 9 records from A taxonomic revision of the ground spiders of the genus Apopyllus (Araneae: Gnaphosidae). 1 records from Myriapoda - SMF. 1437 records from (Figure 4) Palynological results across the PETM of ODP Hole 189-1172D. 536 records from Natural History Museum, Vienna - Herbarium W. 13 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 5 records from Phytoplankton samples - 2001/02 V7 LOSS. 537 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 939 records from Macaulay Library Audio and Video Collection. 138 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 18 records from Mollusk Collection of Yokosuka City Museum. 3 records from Ichthyology, Kagoshima University Museum. 204 records from Harold W. Manter Laboratory of Parasitology Collection. 2 records from Tartu University, palaeontology collections. 1 records from Ohio State University Fish Division (OSUM). 60 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV5. 1 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 28 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 7 records from Tab. 1 + 2: Distribution chart of nannoplankton species record. 555 records from Field Museum of Natural History (Botany) Fungi Collection. 40 records from Nekton and plankton counts from RMT (320 µm) hauls of cruise GAE 1975/76. 107 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 10653 records from NMNH Extant Specimen and Observation Records. 1 records from ARC-PPRI: National Survey of Arachnida (1905-2009). 1 records from DSMZ Collection of Filamentous Fungi and Yeasts. 5 records from The Fungal Collection of Helga Große-Brauckmann at the Botanische Staatssammlung München. 245 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from Collection Copepoda - SMF. 2 records from Collection Soil Aninmals. 1 records from Corvids Literature Database. 8 records from Edaphobase. 407 records from Partial Amphibians Collection. 530 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 1427 records from Mountain Invasion Research Network (MIREN) survey. 125 records from Swiss Psyllid (Hemiptera) Collections - Basel. 86 records from Parasitic Platyhelminthes Collections. 592 records from SOMBASE. 373 records from ANTARCTIC PLANT DATABASE. 88 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 9626 records from Seabirds of the Southern and South Indian Ocean. 2274 records from Australian Antarctic Division Herbarium. 5107 records from ARGOS Satellite Tracking of animals. 594 records from National Whale and Dolphin Sightings and Strandings Database. 1619 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 17 records from Cetacean Sightings Survey and Southern Ocean cetacean program. 46 records from Canadian Museum of Nature Herbarium. 177 records from UWBM Mammalogy Collection. 366 records from UWBM Ornithology Collection. 14 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 16 records from UWFC Ichthyology Collection. 8 records from UF Florida Museum of Natural History Mammals. 2 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 103 records from The AAU Herbarium Database. 312 records from Real Jardin Botanico, Madrid: MA-Musci. 3 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 2 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 1114 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 6 records from CIBIO, Alicante:ABH-GBIF. 392 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1 records from NYSM Mammals. 193 records from Herbario de la Universidad de Sevilla. 91893 records from HMAP-History pf Marine Animal Populations (CoML). 12250 records from NODC WOD01 Plankton Database. 2408 records from SeamountsOnline (seamount biota) (CoML). 1100 records from Natural Geography In Shore Areas (NaGISA) Dataset. 6 records from Bishop Museum Data (OBIS distribution) (USOBIS). 26 records from Generic Taxonomic Database System on Mysida and Nematoda. 230 records from Academy of Natural Sciences OBIS Mollusc Database. 1627 records from SEAMAP - marine mammals, birds and turtles. 568 records from Hexacoral Database. 2 records from Atlantic Reference Centre (OBIS Canada). 1 records from Canadian Museum of Nature - Fish Collection (OBIS Canada). 192582 records from Auckland Museum Botany Collection. 314852 records from ``South Western Pacific Regional OBIS Data provider for the NIWA Marine Biodata Information System``. 68 records from ChEssBase (CoML). 3286 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 821 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2732 records from Fishes in the Argentine Sea from 1967 to the present time. 440 records from AIMS - Bioresources Library (OBIS Australia). 139 records from Natal Museum - Mollusc Collection (AfrOBIS). 1264 records from iziko South African Museum - Fish Collection (AfrOBIS). 43 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 18836 records from Marine and Coastal Management - Copepod Surveys (AfrOBIS). 123 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 1762 records from iziko South African Museum - Shark Collection (AfrOBIS). 89 records from iziko South African Museum - Mollusc Collection (AfrOBIS). 470 records from Distribution ashore and breeding places of southern elephant seals. 529 records from Cetacean distribution in the South Atlantic and South Pacific Ocean (AR-OBIS). 959 records from Marine and Coastal Management - Demersal Surveys (years 1983-1985) (AfrOBIS). 10213 records from Marine and Coastal Management - Demersal Surveys (years 1986-1990) (AfrOBIS). 16551 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 4535 records from Marine and Coastal Management - Demersal Surveys (years 1996-2000) (AfrOBIS). 6364 records from Marine and Coastal Management - Demersal Surveys (years 2001-2005) (AfrOBIS). 1343 records from Marine and Coastal Management - Demersal Surveys (years 2006-) (AfrOBIS). 123133 records from MICROBIS database. 493 records from Polycystine Radiolarians from the water column and the surface sediments of the World Ocean. 71 records from Distribution of nematodes in Patagonia Argentina coast (OBIS South America, SOUTHERN OCEAN SUB-NODE). 28 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 851 records from Michigan State University Herbarium Lichens. 287 records from BYU Herpetology Collection. 175 records from LSUMZ Mammals Collection. 14128 records from Paleobiology Database. 28 records from Fish collection of National Museum of Nature and Science. 2473 records from Individual Sightings. 2694 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 231 records from Mammals Specimens. 53 records from SDNHM Birds Collection. 2 records from SDNHM Herpetology Collection. 1 records from Arizona State University Amphibian and Reptile Collection. 3869 records from Arizona State University Lichen Collection. 439 records from Galathea II, Danish Deep Sea Expedition 1950-52. 3 records from Botanical Museum, Copenhagen. Database of type specimens. 50 records from DAV UC Davis Center for Plant Diversity. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 28 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2 records from Herbarium (UNA). 1 records from CNMA/Colección Nacional de mamíferos. 1 records from MEXU/Tipos de plantas vasculares. 433 records from MEXU/Colección de Briofitas. 9 records from Plants of Papua New Guinea. 749 records from Mammal specimens. 2 records from MMNH Museum Bird Collection. 69 records from Invertebrate Paleontology Division, Yale Peabody Museum. 1827 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 16 records from Invertebrate Zoology Division, Yale Peabody Museum. 27 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 248 records from TTU Mammals Collection. 18 records from Algaterra Types. 105 records from Herbarium Berolinense. 2536 records from Lichen Herbarium Berlin. 300 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 476 records from Biologiezentrum Linz. 693 records from United States National Plant Germplasm System Collection. 359 records from The System-wide Information Network for Genetic Resources (SINGER). 95 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 8 records from The Erysiphales Collection at the Botanische Staatssammlung München. 142 records from The Erysiphales Collection at the University Halle-Wittenberg. 14 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Collection of Hermann Neubert. 13 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 6 records from IndOBIS, Indian Ocean Node of OBIS. 34 records from Nordic Genetic Resources. 81 records from USU-UTC Specimen Database. 13080 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 28 records from Pelagic Fish Observations 1968-1999. 292 records from UF Invertebrate Zoology. 381 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 7 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 57 records from Fish Collection of Natural History Museum and Institute, Chiba. 2 records from HBGSpermatophyta - Herbarium Hamburgense. 1 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 1334 records from South Western Pacific Regional OBIS Data Asteroid Subset (South Western Paci fic OBIS). 3379 records from South Western Pacific Regional OBIS Data Bryozoan Subset (South Western Paci fic OBIS). 24928 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 45 records from Inventory of Antarctic seabird breeding sites. 76 records from Electron Micrograph Database - Marine Specimens. 4 records from Kelp rafts in the Southern Ocean. 38 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 70 records from Harvard University Herbaria. 9 records from DSMZ Prokarya Collection Catalogue. 99 records from EURISCO, The European Genetic Resources Search Catalogue. 76 records from Electron Micrograph Database (Australian Antarctic Data Centre). 28 records from Pelagic Fish Observations 1968-1999 (Australian Antarctic Data Centre). 4 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 85 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 4414 records from MAL. 1599 records from Planktic foraminifera assemblage of sediment core ELT45.029-PC. 2115 records from Planktic foraminifera assemblage of sediment core ELT49.021-PC. 284 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean. 2409 records from Planktic foraminifera counts in surface sediment samples. 42 records from Planktic foraminiferal assemblage for the 10kyr time slice from different sediment cores. 121 records from Distribution of planktonic foraminifera in surface sediment samples A180-072 to V23-83. 918 records from Modern planktic foraminifera assemblage from surface sediment samples used as reference data set for the reconstruction of Atlantic sea surface temperatures during the last glacial maximum (LGM). 383 records from Distribution of planktic foraminifera at the last glacial maximum. 125 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 2015 records from Distribution of planktic foraminifera, factor analysis, SST of sediment core PS2495-3. 1182 records from Distribution of planktic foraminifera, factor analysis, SST of sediment core PS2498-1. 669 records from Relative abundance of planktic foraminifera in sediment core SO136-011GC. 122 records from Distribution of planktic foraminifera in surface sediment samples from cruise SO136. 2348 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 515 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 354 records from Time slice 2 of planktic foraminifera of the last glacial maximum. 470 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 86 records from Foraminifera and stable isotopes of sediment core PS2076-1. 3139 records from Foraminifera and stable isotopes of sediment core PS2076-3. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 400 records from Abundance of planktonic foraminifera in surface sediments of the South Atlantic. 518 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-120. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 772 records from Relative abundance of planktic foraminifera in sediment core RC08-39. 1608 records from Stable isotope analysis of benthic foraminifera and summer sea surface temperature reconstruction of sediment core PS2489-2. 4948 records from (Table T1) Abundance of planktic forminifera in ODP Site 177-1090. 567 records from Naturalis Biodiversity Center (NL) - Aves. 21 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 4 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 242 records from (Fig. 3) Age and multiproxy studies of sediment core GeoB7186-3. 4 records from University of Alberta Museum of Zoology Amphibian and Reptile Collection (UAMZ). 1284 records from Mosquito Occurrence Dataset. 16 records from ANTXXIII-8 Birds and Mammals. 242 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 50 records from Collections data on ecology of bottom animal of the Southern ocean. 14 records from Nemertina World Checklist. 11 records from Christopher Walker collection of Glomeromycotan fungi. 1 records from Invertebrates compiled by W.Block. 1 records from UCM Amphibian and Reptile Collection (Arctos). 1810 records from (Appendix C) Distribution of benthic foraminifera in surface sediments from the Chatham Rise. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 1913 records from (Appendix B2) Distribution of planktic foraminifera in ODP Hole 181-1125A east of New Zealand. 339 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 15825 records from Field Museum of Natural History (Botany) Bryophyte Collection. 17 records from CSIRO, Cruise SS199101, Marine Biology Data, Western Australia, 1991. 13 records from Phytoplankton abundance in surface water during Akademik Vernadsky cruise AV24. 8 records from Fundación Miguel Lillo - Colección Ornitológica. 1 records from Mammifères (sauf Chiroptères) du Muséum d'Histoire Naturelle de la ville de Bourges (BOUM). 25807 records from Seabird Atlas of South-eastern Australian Waters. 3 records from USF Herbarium. 98 records from (Figure 6k and 6l) Nannofossil accumulation rate and absolute abundances of coccoliths from ODP Site 1233. 9 records from New species and phylogenetic relationships of the spider genus Coptoprepes using morphological and sequence data (Araneae: Anyphaenidae). 29 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 90 records from Quaternary radiolarians from offshore eastern New Zealand, ODP Leg 181, Site 1123, relative abundances. 1124 records from Relative abundance of organic-walled dinoflagellate cysts in surface sediments. 1080 records from Distribution of major planktic foraminifer at Site 177-1088. 1134 records from Distribution of major planktic foraminifera at Site 177-1089. 2646 records from Distribution of major planktic foraminifer at Site 177-1090. 2 records from Planktic foraminifera abundance of Hole 39-358. 373 records from Planktic foraminifera abundance of Hole 26-251. 963 records from Planktic foraminifera abundance of Hole 26-251A. 149 records from Planktic foraminifera abundance of Hole 29-282. 284 records from Planktic foraminifera abundance of Hole 29-284. 23 records from Planktic foraminifera abundance of Hole 29-284A. 692 records from Planktic foraminifera abundance of Hole 40-360. 3379 records from (Table 14A) Occurrences of planktonic foraminifers in DSDP Hole 90-592, samples 592-1-CC through 592-29-CC. 2310 records from (Table 15A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-593. 210 records from (Table 15C) Occurrences of planktonic foraminifers in Hole 90-593A. 237 records from Planktic foraminifera abundance of Hole 21-207. 345 records from Planktic foraminifera abundance of Hole 21-207A. 1322 records from Planktic foraminifera abundance of Hole 29-284. 205 records from Planktic foraminifera abundance of Hole 29-284A. 8 records from PSM Vertebrates Collection. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña marzo 2007. 81 records from KUBI Ichthyology Collection. 800 records from Natural History Museum, University of Tartu. 429 records from Planktic foraminifera abundance of Hole 40-360. 83 records from Planktic foraminifera abundance of Hole 40-361. 999 records from University of British Columbia Herbarium (UBC) - Algae Collection. 4 records from MLZ Bird Collection (Arctos). 4 records from Herbarium of Umeå University (UME). 16541 records from Field Museum of Natural History (Botany) Seed Plant Collection. 136 records from Colección Nacional de Entomología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 97 records from Range table from planktonic foraminifers in ODP Hole 177-1088C. 132 records from Range table from planktonic foraminifers in ODP Hole 177-1089A. 37 records from MBML-Herbario - Herbário Mello Leitão. 98 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 108 records from Range table from planktonic foraminifers in ODP Hole 177-1089C. 59 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 19 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 6 records from MPM Milwaukee Public Museum Herbarium. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 868 records from (Table 3) Planktic foraminiferal abundance in Oligocene to Early Pliocene sediments of ODP Hole 177-1090D on the Agulhas Ridge, South Atlantic. 285 records from (Table 4) Planktic foraminiferal abundance in Oligocene to Early Miocene sediments of ODP Hole 177-1090E on the Agulhas Ridge, South Atlantic. 2 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 525 records from Benthic foraminifera abundance of Hole 40-360. 284 records from Benthic foraminifera and nannofossil abundance of Hole 40-360. 13 records from Range table from benthic foraminifers in ODP Hole 177-1088B. 109 records from Range table from benthic foraminifers in ODP Hole 181-1119B. 357 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 30 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 31 records from Range table from benthic foraminifers in ODP Hole 181-1123B. 47 records from Range table from benthic foraminifers in ODP Hole 181-1123C. 35 records from Range table from benthic foraminifers in ODP Hole 181-1124C. 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 15 records from Range table from benthic foraminifers in ODP Hole 189-1172D. 9522 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from MBML-Anfibios - Coleção de Anfíbios MBML. 1 records from Homoptera. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 1 records from Dinoflagellate abundance of Hole 21-207A. 4 records from Dinoflagellates, pollen and spore abundance of Hole 29-282. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 3 records from Dinoflagellates, pollen and spore abundance of Hole 29-284. 15 records from Microfossil abundance of Hole 39-358. 271 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1168A. 144 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1172A. 109 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1172D. 387 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 559 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 16 records from Diversity of total live benthic foraminiferal assemblages in South Atlantic surface sediments. 28 records from Diversity of live benthic foraminiferal assemblages in South Atlantic surface sediments. 34 records from Diversity of dead benthic foraminiferal assemblages in South Atlantic surface sediments. 724 records from Dead benthic foraminifera in South Atlantic surface sediments. 1667 records from Relative abundance of deep-sea benthic foraminifera in surface sediments east of New Zealand. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 4 records from KUBI Invertebrate Zoology Collection. 1 records from R. L. McGregor Herbarium Lichen Collection. 3 records from R. L. McGregor Herbarium Vascular Plants Collection. 3 records from ANDEEP3: SeaStars (Echinodermata, Asteroidea). 87 records from ABBBS Bird Banding records from the Australian Antarctic Territory and Heard Island.. 566 records from Senckenberg - CeDAMar Resource. 420 records from Texas A&M University Insect Collection. 29 records from UAZ Mammals. 160 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 239 records from COMARGIS: Information System on Continental Margin Ecosystems. 8 records from Botany Division, Yale Peabody Museum. 1 records from Entomology Division, Yale Peabody Museum. 48 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 1 records from Paleobotany Division, Yale Peabody Museum. 4 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 4 records from Whale log - observations from ANARE voyages. 814 records from BIOLOGICAL SCIENCES DATA. 24 records from Collection Pisces SMF. 58 records from Collection Arachnology SMF. 43 records from Collection Porifera SMF. 85 records from Collection Polychaeta SMF. 477 records from Collection Aves (spirit preserved) SMF. 40 records from Collection Cnidaria SMF. 49 records from Herbarium Senckenbergianum (FR). 3 records from Collection Aves (bird skeletons) SMF. 495 records from Collection Aves (bird skins) SMF. 43 records from Collection Crustacea SMF. 226 records from Collection Bryozoa SMF. 3 records from Collection Echinodermata SMF. 231 records from SINGER Coordinator. 1 records from NHT_flora. 195 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 75 records from Database of Native Plants in Taiwan. 557 records from AMNH Bird Collection. 61 records from AMNH Mammal Collections. 37 records from Siliceous microfossil occurrence, Site 177-1088. 18 records from Lost and found: the Plecoptera types of Blanchard and Mabille, with further contributions to the stoneflies of Chile. 149 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1172A. 46 records from Ophiuroidea collections of the Zoological Institute Russian Academy of Sciences. 23 records from University of Florida Invertebrate Paleontology. 138 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 2 records from Ditsong National Museum of Natural History Collection: 1805-2008. 7 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 139 records from SMNS Herpetologie. 55 records from MVZ Egg and Nest Collection (Arctos). 307 records from Museum of Southwestern Biology, Division of Arthropods. 3623 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ornithology National Collection (MACNOr).. 9603 records from Seabird Observations, Storm Bay, Tasmania, Australia, 1991-1994. 3623 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 517 records from Distribution ashore of Southern elephant seals in Península Valdés. 13 records from (Table 5) Distribution of calcareous nannofossil species at DSDP Hole 40-361. 132 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 1 records from Revision of the genus Euthalenessa Darboux (Polychaeta: Sigalionidae). 2 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 2 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 16 records from Naturalis Biodiversity Center (NL) - Porifera. 26 records from UPCB - Herbário do Departamento de Botânica. 2 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 16866 records from Gravel Master Thesis / Chubut, Argentina. 7 records from Collection ornithologique A. Maës. 14061 records from Queensland Museum provider for OZCAM. 2 records from ARC-PPRI: Collection of Southern African bees (1800-2007). 275 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in Quaternary sediments from ODP Hole 189-1172A. 19033 records from Bureau of Rural Sciences, Commercial Fisheries Presence, Australia, 2000-2002. 4 records from CM Birds Collection. 15 records from CUMV Amphibian Collection (Arctos). 32 records from NMSA: Arthropod Collections (1900-2012). 1207 records from Lund Botanical Museum (LD). 5966 records from Auckland Museum Land Vertebrates Collection. 12321 records from Snow Entomological Museum Collection. 1 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XXII/3 (ANDEEP III). 9 records from Spider Mites Collection of Jean Gutierrez. 1380 records from (Table 16) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-593. 18840 records from Geographically tagged INSDC sequences. 104 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 63 records from Ouellet-Robert entomological collection (QMOR). 114 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 7 records from Field Museum of Natural History (Botany) Lichen Collection. 5 records from TEPB - Herbário Graziela Barroso. 5 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 50 records from Field Museum of Natural History (Zoology) Fish Collection. 1 records from The First Parthenogenetic Pleurodont Iguanian: A New All-female Liolaemus (Squamata: Liolaemidae) from Western Argentina. 1853 records from MSB Mammal Collection (Arctos). 62 records from MSB Host Collection (Arctos). 2 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 131 records from Ghent university - Zoology Museum - Nematod Collection. 2 records from William Nylander lichen collection. 1832 records from Geographic distribution of dinoflagellate cysts in surface sediments. 434 records from ARC-PPRI: Chalcidoidea Collection (1900-2010). 1228 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 67 records from LGM, planktic foraminifera (EPILOG version). 2 records from Colección de Herbario. 9 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 10533 records from SAFRING: Historical Bird Ringing Records (2005-2009). 6 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from R-Tipos - Herbário do Museu Nacional - Tipos. 242 records from The cnidarians collection (IK) of the Muséum national d'Histoire naturelle (MNHN - Paris). 732 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 62 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 241 records from NORFANZ Biological Survey, Tasman Sea, Australia - New Zealand 2003. 6 records from University of Tennessee at Chattanooga. 14 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 6 records from The Fish Database of Taiwan. 3 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 6884 records from CSIRO, Abundance and distribution of orange roughy in southeast Australian waters 1987-1979. 1150 records from Bernice P. Bishop Museum. 6 records from DNSM: Durban Natural Science Museum Insect Collection (1900-2011). 12 records from CUMV Reptile Collection (Arctos). 37 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 24 records from Cowan Tetrapod Collection - Birds. 1 records from Hyalinecia (sic) Edwardsi Roule, 1898 — the enigmatic ghost from abyssal depths—redescribed as Nothria edwardsi (Annelida: Onuphidae). 2 records from Carnet en Ligne. 2 records from World flea collection of Slovenian Museum of Natural History (excluding Slovenia). 18 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 779 records from UMMZ Birds Collection. 34765 records from Australian National Insect Collection. 1471 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 3854 records from Royal Botanic Garden Edinburgh Herbarium (E). 114 records from Colección de Entomología - Coleoptera. 28 records from Colección de Entomología - Hymenoptera - Aculeata. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 1 records from ZUEC-PIS - Coleção de Peixes do Museu de Zoologia da UNICAMP. 164 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Arroyo Sauce Grande (Monte Hermoso). 1 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 403 records from Botany (UPS). 62267 records from European Molecular Biology Laboratory Australian Mirror. 2 records from The Ando-Patagonian Stigmella magnispinella group (Lepidoptera, Nepticulidae) with description of new species from Ecuador, Peru and Argentina. 81 records from Instituto de Ciencias Naturales. 4312 records from (Table 18) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-593. 2 records from DMNS Egg Collection (Arctos). 51 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 362 records from Mammalogy Collection - Royal Ontario Museum. 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 949 records from (Table 19) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-593. 3 records from Census of Cnidaria (Medusozoa) and Ctenophora from South American marine waters. 1290 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 303 records from NMNH Paleobiology Specimen Records. 1060 records from Programa de Observadores a Bordo (POBCh) de la Secretaria de Pesca de la Provincia del Chubut, Argentina . Observer On board Program -Fisheries Secretariat of the Province of Chubut-Argentina (OOBPPCh). 22 records from Insect Occurrence Data from MIZA. 2 records from University of British Columbia Herbarium (UBC) - Fungi Collection. 1 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 2 records from EAC - Herbário Prisco Bezerra. 10 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 4 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 395 records from (Appendix C) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 2 records from University Of Pretoria: Lacewing Database Project (1911-2015). 503 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 73 records from Colección de Entomología - Heteroptera. 1295 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 28 records from Herpetology Collection - Royal Ontario Museum. 1491230 records from Garden Bird Surveys. 233 records from CAS Herpetology (HERP). 2 records from MBML-Repteis - Coleção de Répteis. 8 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 1 records from Ictiologia Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Scleractinia of Eastern Australia - AIMS Monograph Series - John (Charlie) Veron. 4 records from Vascular plant herbarium, Tromsø Museum. 79865 records from Queen Victoria Museum Art Gallery provider for OZCAM. 16 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 9 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 1660 records from Catch records from eddy studies off the New South Wales coast, Australia 1979-1980. 22161 records from New Zealand Biodiversity Recording Network. 373 records from Observaciones de Especies Silvestres (by Charif Tala). 230 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 6 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 286 records from Colección de Entomología - Hymenoptera - Parasitica. 7 records from Global compendium of Aedes aegypti occurrence. 1 records from Worldwide revision of the genus Fraseroscyphus Boero and Bouillon, 1993 (Cnidaria: Hydrozoa): an integrative approach to establish new generic diagnoses. 7148 records from Free-living marine Nematodes from San Antonio bay (Río Negro, Argentine) 2009.. 62 records from Natural History Museum Rotterdam (NL) - Insecta collection. 2 records from The French Collection of Medicago truncatula. 19 records from NCSM Invertebrates Collection. 75 records from UB - Herbário da Universidade de Brasília. 35 records from Naturalis Biodiversity Center (NL) - Mollusca. 2 records from Catalogue of Afrotropical Bees. 21 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 3 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 18 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña noviembre 2006. 290 records from (Table 2) Live benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 789 records from KUBI Herpetology Collection. 164772 records from Australian Museum provider for OZCAM. 51 records from Colección de Entomología - Orthoptera. 1 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1239 records from (Appendix Table 2) Relative abundances of calcareous nannofossil in the >4 µm assemblage of ODP Hole 177-1090D. 1 records from On the genus Trachysalambria Burkenroad, 1934 (Crustacea, Decapoda, Penaeidae), with descriptions of three new species. 61 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 5 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 2413 records from Registros de hongos en áreas protegidas de la Argentina. 4 records from University of Pretoria: Dung Beetles (Coleoptera: Scarabaeidae: Scarabaeinae). 110711 records from Allan Herbarium (CHR). 18 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 21 records from NOAA Deep Sea Corals Research and Technology Program. 3 records from Cowan Tetrapod Collection - Herpetology. 3725 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Mammalogy National Collection (MACNMa).. 109 records from Entomology at ZMUC, Natural History Musem of Denmark. 1 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 25 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 1 records from HPL - Herbário do Jardim Botânico Plantarum. 1 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 5651 records from Neptune Deep-Sea Microfossil Occurrence Database. 757 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 11928 records from Auckland Museum NZ Marine Collection. 12 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 721 records from MVZ Bird Collection (Arctos). 1698 records from Vascular Plant Herbarium, Oslo (O). 3 records from Occurrences in SinBIOTA. 192 records from KUBI Ornithology Collection. 1099 records from Anymals+plants - Citizen Science Data. 5 records from Clarification of Einfeldia Kieffer, 1922 (Diptera: Chironomidae) with E. australiensis (Freeman, 1961), comb. n. based on immature stages. 1307 records from Lichen herbarium, Tromsø Museum. 6 records from CSIRO, fish surveys by the Courageous, 1978-1979. 1 records from E. C. Smith Herbarium (ACAD). 1 records from UAIC Ichthyological Collection. 9 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 5 records from Taxonomic review of the species of Helina R. - D. (Diptera: Muscidae) from Andean-Patagonian forests. 2 records from NCSM Mammals Collection. 10 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2010. 32 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 149 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 92 records from UF FLMNH Ichthyology. 12070 records from Auckland Museum Marine Collection. 8 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 60240 records from New Zealand Fungal and Plant Disease Collection (PDD). 792 records from (Table 13) Benthic foraminifera in early-mid Miocene sediments of DSDP Hole 90-592. 33 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 902 records from (Table 14B) Occurrences of planktonic foraminifers in DSDP Hole 592, samples 592-30-CC through 592-41-CC. 3 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 857 records from Marine Invertebrate from Argentina, Uruguay and Chile. 205 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 2678 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 168 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 16 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 32 records from Fundación Miguel Lillo - Colección Criptogámica. 3 records from SysTax - Herbaria. 6081 records from Censos de aves del parque nacional Laguna Blanca. 5 records from A review of the Australian endemic clam shrimp, Paralimnadia Sars 1896 (Crustacea: Branchiopoda: Spinicaudata). 2839 records from Geneva Herbarium – General Collection (G). 1810 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 31977 records from Instituto de Botánica Darwinion. 4557 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 4837 records from Free-living marine Nematodes from San Antonio and Cormoranes sandy beaches (Rio Negro, Argentina), 2006.. 4 records from UFMT - Herbário UFMT. 2 records from CAS Botany (BOT). 22 records from CUMV Bird Collection (Arctos). 42557 records from South Australian Museum Australia provider for OZCAM. 295 records from International Fossil Shell Museum (NL) - Mollusca Collection. 354 records from Lichen herbarium, UiB. 4 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 2 records from HEPH - Herbário Ezechias Paulo Heringer. 1 records from CHAS Oology Collection (Arctos). 3 records from HRCB - Herbário Rioclarense. 2 records from PACA-AGP - Herbarium Anchieta. 8 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Millenium Seedbank (MSB). 3 records from UESC - Herbário Universidade Estadual de Santa Cruz. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences